2012
DOI: 10.3856/vol40-issue1-fulltext-10
|View full text |Cite
|
Sign up to set email alerts
|

From coexistence to competitive exclusion: can overfishing change the outcome of competition in skates (Chondrichthyes, Rajidae)?

Abstract: ABSTRACT.Competition for food could be a major force driving changes in the community structure of skates (Rajidae) subjected to fishing exploitation. Under this hypothesis, small skates are released from competition with larger skates after fishing has depleted the larger species. Here, we compare the abundance patterns of two sympatric skates with similar niches but different life histories, Bathyraja albomaculata (larger and slow-reproducing) and Bathyraja macloviana (smaller and faster-reproducing), before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Bathyraja albomaculata is the smallest of the four predominant Falkland species but can still be susceptible to fishing pressure. Ruocco et al () found that on the south‐eastern Patagonian shelf, abundance of B. albomaculata decreased since development of a trawl fishery, while abundance of a smaller skate Bathyraja macloviana (Norman 1937) increased. Ruocco et al () concluded that different populations of B. albomaculata could be present in the south‐west Atlantic Ocean, in which case the Falkland Islands might have a local population that is not buffered over a broader spatial range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bathyraja albomaculata is the smallest of the four predominant Falkland species but can still be susceptible to fishing pressure. Ruocco et al () found that on the south‐eastern Patagonian shelf, abundance of B. albomaculata decreased since development of a trawl fishery, while abundance of a smaller skate Bathyraja macloviana (Norman 1937) increased. Ruocco et al () concluded that different populations of B. albomaculata could be present in the south‐west Atlantic Ocean, in which case the Falkland Islands might have a local population that is not buffered over a broader spatial range.…”
Section: Discussionmentioning
confidence: 99%
“…Significant abundance increases of some species but not others may nevertheless signal changes in the composition of the assemblage under continuing exploitation. In the south‐west Atlantic (Ruocco et al , ) and north‐east Atlantic (Walker & Heessen, ; Walker & Hislop, ; Dulvy et al , ), changes in skate species composition have shown increasing abundances of small species as large species decreased. In the north‐west Atlantic, changes have been less clearly related to size (Stevens et al , ; Swain et al , ), although life‐history analyses have also indicated that larger species are more vulnerable to decline (Frisk et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Bathyraja macloviana is a benthic predator that feeds mainly on polychaetes followed by amphipods, isopods and decapods. This results agree with published information on diet composition of this species in the same region (Mabragaña et al ., 2005;Scenna et al ., 2006;Ruocco et al ., 2012). Many species of elasmobranchs such as B. macloviana are not top predators, and have received little attention, with the potential effects of these predators dismissed in ecological systems (Vaudo & Heithaus, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Females mature between 520 and 540 mm L T , whereas males mature between 519 and 535 mm L T (Paesch & Oddone, 2009). Bathyraja macloviana is a benthophagous fish that feeds mainly on polychaete worms and a small proportion of amphipods, isopods and decapods (Mabragaña et al ., 2005;Scenna et al ., 2006;Ruocco et al ., 2012). Although these studies provide important data on the diet composition of B. macloviana, no information about the interactions among intrinsic and extrinsic factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…reducing predation) or indirectly (i.e. reducing competition) af fect other species of the marine community (Stevens et al 2000, Shepherd & Myers 2005, Ruocco et al 2012, since they are key species in most ecosystems (Stevens et al 2000). Despite the key role that elasmobranchs play in ecosystems, the basic biological information needed for responsible management is lacking for many species, including minimum, maximum and average sizes, age-at-maturity estimations and lengthto-weight relationships.…”
Section: Introductionmentioning
confidence: 99%